Improvement of program-goal method in defence planning system - Федоренко, Р.М.; Казак, В.М. (Proceedings of National Aviation University (archive), 2005)
The article proposes the conception of defence planning system development with program-goal method application that based on analysis of advanced experience of developed countries. Article specified the place of program-goal method in resolving defence planning tasks of national security.